A Simple Rational Expectations Keynes-Type Model - Bryant, John (Quarterly Journal of Economics, 1983)
Journal Article A Simple Rational Expectations Keynes-type Model Get access John Bryant John Bryant Rice University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 98, Issue 3, August 1983, Pages 525–528, https://doi.org/10.2307/1886025 Published: 01 August 1983